2017
DOI: 10.3390/su9081427
|View full text |Cite
|
Sign up to set email alerts
|

Social Enterprise as a Catalyst for Sustainable Local and Regional Development

Abstract: This study aims to present an integrated theoretical framework of sustainable local and regional development with an emphasis on social economy theory. The theoretical literature on social economy and sustainable local and regional development are reviewed and integrated focusing on the obstacles of sustainability and the function of social economy in local and regional development. Conflict and competition among sustainability values necessitates agreement and cooperation among those who embrace such values. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 97 publications
(114 reference statements)
2
48
0
7
Order By: Relevance
“…The process by which individuals living in neighborhoods actively intervene in ways that discourage problematic behavior has been termed "collective efficacy" [52] (pp. [10][11]. On the other hand, researchers have concluded that contrary to Jane Jacobs's (1961) suggestion, commercial uses are associated with increased crime rates.…”
Section: The Taxonomical Globality Of Cities and The Search For A Newmentioning
confidence: 99%
See 1 more Smart Citation
“…The process by which individuals living in neighborhoods actively intervene in ways that discourage problematic behavior has been termed "collective efficacy" [52] (pp. [10][11]. On the other hand, researchers have concluded that contrary to Jane Jacobs's (1961) suggestion, commercial uses are associated with increased crime rates.…”
Section: The Taxonomical Globality Of Cities and The Search For A Newmentioning
confidence: 99%
“…However, places and their economies can be viewed more socially, as a set of relationships and practices ranging from everyday family and community life to norms of consumption, to the social regulation of work habits, and to professional practices. The concept of sustainability then offers an alternative perspective on territorial development and transformation, which promotes innovation in social relations [11] (pp. [4][5].…”
Section: Introduction: Sustainability Reputation Of the Cities And mentioning
confidence: 99%
“…RJCP is a federal government program that started in 2013 to support unemployed people in building skills to become "work ready" or to participate in activities that contribute to the strength and sustainability of their community (Australian Government, 2015b) [2]. Importantly, these activities allow Nuwul to maximize community input into the environmental management of the northeast Arnhem Land region both directly through activities and indirectly through the influence and gained understanding from teaching other life skills:…”
Section: An Indigenous Social Enterprise In Remote Northeast Arnhem Lmentioning
confidence: 99%
“…Other authors explicitly consider team production and collective action as founding principles of entrepreneurial action and innovation processes in new business environments, highlighting also the special role of intrinsic and prosocial motivations in innovation and growth processes [22,23]. However, to the best of the author's knowledge, no contribution has systematically analyzed the corporate patrimony within the common property approach, and explicitly discussed, in this line of enquiry, the specific features, sustainability (economic and social) and longevity of "alternative" or "heterodox" enterprise forms, such as co-operative and social enterprises [24][25][26]. Few exceptions of approaches similar to the one followed in this paper are found in some works concerning capital resources in worker co-operatives [27], and co-operative finance [28].…”
Section: Introductionmentioning
confidence: 99%